Adult health & human capital : impact of birth weight and childhood growth - Bhargava, Santosh K. (SAGE Publications India Pvt Ltd, 2017)
Chronicles the five-decade journey of the New Delhi Birth Cohort, founded in an era when the nature and sustainability of such investigation was considered unthinkable.